Educational values in bungo community palabe and its relevance as indonesian language teaching materials in preschools - Moonthana Indhra, Feerlie; Yundi Fitrah, Yundi Fitrah; Nazurty, Nazurty; Kusmana, Ade (Jurnal Konseling dan Pendidikan, 2025)
This study aims to describe the educational values in the Palabe of the Bungo community and its relevance as an Indonesian teaching material in PAUD. The method used is qualitative descriptive with content analysis. The research data is in the form of words, sentences, and expressions in Palabe that contain educational value. The source of data was obtained from informants who understood and could speak Palabe well. Hermeneutic techniques are used in data collection and analysis. The results of the study found 23 Palabe of the Bungo community, including the Origin of Siri Sekapur Hamlet, Bujang Datun, Karaketu Bird, Ingenious Chicken Mother, Grandma Ale, Golden Horned Deer, Tampang Eggplant, and Tuanku Sri Titled Imam Sakti. Of the 23 Palabes, four categories of educational values were found, namely religious (74 data), moral (92 data), social (75 data), and cultural (70 data). Religious values include belief, worship, and practice; moral values include patience, tawakal, and a helping attitude; social values involve caring, togetherness, and friendship; While cultural values reflect beliefs, art, customs, and habits. From these values, 14 dominant values were found that are relevant for Indonesian teaching materials in PAUD, including faith, practice, patience, diligence, caring, brotherhood, togetherness, and customs. These values support children's language development, such as understanding commands, appreciating reading, answering questions, composing simple sentences, and enriching vocabulary. Based on the PAUD curriculum, Palabe can be used as a teaching material that supports aspects of early childhood language development, both in understanding and language expression.